Characterization and Quantification of Phenolic Compounds in the Extract of Teak (Tectona grandis Lin. f) Fruits - NATALYA KRISHNAMBIKA; K. SUDHAKARA (Seed Research, 2026)
The present study was conducted at College of Forestry, Kerala Agricultural University, Thrissur, to investigate the presence of major phenolic compounds and to estimate the total phenolic content occurring in the pericarp of fresh and one year old teak fruits obtained from Nilambur Forest Division. Characterisation of the phenolic compounds was done using Thin Layer Chromatography and the quantification of the total phenolic content was done using colorimetry. It was found that phenolic compounds occurring in the teak fruits are basically hydroxybenzoic acids. These include syringic acid with R, value of 0.79 (in the mesocarp and the endocarp irrespective of the age of the fruits), gentisic acid with an R, value of 0.46 (in the endocarp of one year old fruit), p-hydroxybenzoic acid with an R, value of 0.57 (in the endocarp of fresh fruit), vanillic acid with an R, value of 0.87 (in the mesocarp of one year old fruit) and protocatechuic acid with an R, value of 0.19 (in the mesocarp of fresh fruit). The amount of total phenolic content in the mesocarp of the fruit was relatively higher than those found in the endocarp irrespective of the age of the fruit lot. The total phenolic content with respect to ageing of fruits proved statistically non-significant. The bioassay studies using the leachate of teak fruits are contradictory; this may be due to fact that the physiological effect of hydroxybenzoic acids upon seed dormancy is yet to be verified.